2010
DOI: 10.1007/s11664-010-1254-9
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Amorphous Si0.6Ge0.4 Nanoparticles Embedded in SiO2: Crystallinity Versus Compositional Stability

Abstract: Si 0.6 Ge 0.4 nanocrystals, of diameter <5 nm, embedded in SiO 2 in the form of single layers (2.1 9 10 12 nanoparticles cm -2 ) and five-period multilayers (above 10 13 nanoparticles cm -2 ) have been fabricated using a low-thermalbudget process consisting of deposition by low-pressure chemical vapor deposition and crystallization by rapid thermal annealing at several temperatures and for different times. The crystallization process was monitored by Raman spectroscopy and transmission electron microscopy. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…1(c)]. These results are consistent with the predominant formation of Ge/ Si nano-alloys (Ge/Si-ncs) in regions A and B of the Ge/Si sample and the principal formation of pure Ge-ncs in region C. 17,32,33 Hence, the decrease in the lattice parameter that is measured in the Ge/Si sample is consistent with higher rates of formation of Ge-Si and Si-Si chemical bonds, whose interatomic distance is $3% smaller than that for Ge-Ge. 34 Since the displacement of implanted Si during thermal annealing is less than a few nanometers, 10 we also stipulate that the Raman signature of Si-Si chemical bonds observed in Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…1(c)]. These results are consistent with the predominant formation of Ge/ Si nano-alloys (Ge/Si-ncs) in regions A and B of the Ge/Si sample and the principal formation of pure Ge-ncs in region C. 17,32,33 Hence, the decrease in the lattice parameter that is measured in the Ge/Si sample is consistent with higher rates of formation of Ge-Si and Si-Si chemical bonds, whose interatomic distance is $3% smaller than that for Ge-Ge. 34 Since the displacement of implanted Si during thermal annealing is less than a few nanometers, 10 we also stipulate that the Raman signature of Si-Si chemical bonds observed in Fig.…”
Section: Resultssupporting
confidence: 79%
“…1(d) (peak 4) originates from Si-ncs located in regions A and B of the Ge/Si sample. The presence of a compressive mechanical stress exerted by the surrounding SiO 2 matrix on the formed nanocrystals, 14,32,35 as well as its release for Gencs containing Si, 33 makes the use of Vegard's laws irrelevant to determine the relative concentration of Ge/Si from the lattice parameters given in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of the presence of for any Raman feature can be interpreted as a consequence of the decrease in the amount of material inside the scattering volume. Rodriguez et al [ 14 ] observed a similar behavior, and concluded that, after a certain annealing temperature, the compositional changes due to the out-diffusion of Ge from the crystallized nanoparticles and the associated reduction of the scattering volume cause the NCs to fall below the detection limit of the Raman setup, thus accounting for the disappearance of the Raman signal. The observed absence of Si-Ge and Si-Si Raman peaks for the annealed samples could be explained by the low amount of Si used during the growth and/or a loss of Si atoms during the thermal treatments, which can oxidize and form SiO 2 .…”
Section: Resultsmentioning
confidence: 84%
“…The complete crystallization of the NCs was achieved at temperatures of 800°C and higher [ 8 , 13 , 14 ]. In this article, we report the formation of self-assembled Ge nanoclusters by the magnetron sputtering technique at quite a low deposition temperature of 250°C.…”
Section: Introductionmentioning
confidence: 99%
“…The films formed of GeSi nanocrystals embedded in amorphous SiO 2 matrix, usually prepared by magnetron sputtering or by low‐pressure chemical vapor deposition are investigated. The as‐deposited structures are annealed following an adequate procedure for GeSi nanocrystal formation.…”
Section: Introductionmentioning
confidence: 99%